Breast Cancer and Fatigue - Bardwell, Wayne A. (2008)
Fatigue is a common and disabling symptom in breast cancer patients and survivors. A rather nebulous concept, fatigue overlaps with sleepiness and depressed mood. In this chapter, we cover methods for assessing fatigue; describe the occurrence of fatigue before, during and after initial treatment; present possible underlying mechanisms of fatigue; and, enumerate approaches to its treatment.